Respuestas

2013-04-29T18:56:11+02:00

Solo tienes que usar Algebra de funciones

 

a) (f + g)(2) =

f(2) + g(2) , Reemplazamos

3 * 2 - 2 + 2^3 =

6 - 2 + 8 =

12

por lo tanto , (f+g)(2) = 12

 

b) (f - g)(2) = 

f(2) - g(2) , reemplazamos

3 * 2 - 2 - ( 2^3) =

6 - 2 - 8 =

-4

por lo tanto , (f-g)(2) = -4

 

c)(fg)(2) , lo mismo,

f(2)*g(2)

(3 * 2 - 2 )( 2 ^ 3 )

(4)(8)

= 32

por lo tanto , (fg)(2) = 32

 

d) (f/g)(2) . te debes imaginar como es o no ?...

f(2) / g(2)

4 / 8

= 1/2

por lo tanto , f/g(2) = 1/2.

 

Salu2*